Insight into the Council on Governance of Institutes of Public Character's recommendations. - Wong, Kelvin Wai Wah. (2008)
The aim of this paper is to help reader to better understand the rationale behind the Code and to help deal with the common implementation problems faced by IPCs. The focus of this paper will be on board governance, conflict of interest, financial management and control and disclosure and transparency.